(untitled) (International Journal of Pathology and Genetics of Disease and Nursing Management, 2026)
Neonatal infections remain a major contributor to neonatal morbidity worldwide. In India, the neonatal infection rate is reported to be approximately 44 per 1000 live births, while the incidence of hospital-acquired neonatal sepsis ranges between 1.5% and 37%. Infections in Neonatal Intensive Care Units (NICUs) continue to be a serious concern in both developing and developed countries. A quasi-experimental study using a one-group pretest–post-test design was conducted to evaluate the effectiveness of a Structured Teaching Programme (STP) on nurses’ knowledge and practices related to infection control in NICUs. The study included 300 nurses selected through probability multistage cluster sampling from private hospitals in Kanyakumari District, Tamil Nadu. Data were collected using a structured questionnaire and an observational checklist and analysed using descriptive and inferential statistics. The demographic findings indicated that most nurses (67%) were aged 21–30 years, with the majority holding GNM qualifications (82%), while 13% had B.Sc. Nursing degrees. Nearly half of the participants had 1–5 years (44%) or 5–10 years (43%) of work experience. A large proportion of nurses (93%) reported prior knowledge of infection control, mainly obtained through training (83%). The results showed a notable improvement in knowledge scores, with the mean pretest score of 46.26±8.82 increasing to 70.34±6.52 in the post-test, indicating substantial knowledge gain. Similarly, practice scores improved significantly from a pretest mean of 426.84±26.43 to a post-test mean of 641.23±20.18. Statistical analysis demonstrated a highly significant difference between pretest and post-test knowledge and practice scores (p<0.001), confirming the effectiveness of the Structured Teaching Programme. A significant association was also found between post-test scores and selected demographic variables, and a strong positive correlation (r=0.86) was observed between knowledge and practice scores.